2015
DOI: 10.1002/ajoc.201402286
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Labelling of Host‐Guest Assemblies with Nitroxide Radicals

Abstract: Within the developing interface between free radicals and supramolecular chemistry, nitroxides play a special role because they are stable and easy to functionalize. This Focus Review summarizes recent progress in the design and synthesis of paramagnetic host‐guest complexes characterized by the presence of a nitroxide label covalently linked to the organic macrocycle. Examples include the synthesis of open‐shell, mechanically interlocked molecules (MIMs), such as rotaxanes, in which the dumbbell, the wheel, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 86 publications
2
34
0
Order By: Relevance
“…Another approach to increase stability of nitroxides is their encapsulation in different molecular "containers" such as liposomes, cyclodextrins, cucurbituriles, and calixarenes (Kirilyuk et al, 2010;Mezzina et al, 2015;Woldman et al, 2009). In some cases, e.g., in liposomes, the lifetime of nitroxides increases by several orders of magnitude; yet liposomes cannot be used in vivo.…”
Section: Synthesis Of New Nitroxide-based Spin Probes and Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to increase stability of nitroxides is their encapsulation in different molecular "containers" such as liposomes, cyclodextrins, cucurbituriles, and calixarenes (Kirilyuk et al, 2010;Mezzina et al, 2015;Woldman et al, 2009). In some cases, e.g., in liposomes, the lifetime of nitroxides increases by several orders of magnitude; yet liposomes cannot be used in vivo.…”
Section: Synthesis Of New Nitroxide-based Spin Probes and Labelsmentioning
confidence: 99%
“…Therefore another strategy was pursued. It was shown that encapsulation of nitroxide spin probes can significantly increase their lifetime in reducing media (Kirilyuk et al, 2010;Mezzina, Manoni, Romano, & Lucarini, 2015 (Karoui et al, 2002;Scheme 5). However, this approach suffered from the use of a large amount of CD impeding its implementation in vivo.…”
Section: High Persistence and High Protection Of Spin Adducts Againstmentioning
confidence: 99%
“…The interest in this family of compounds stands in (i) reversible redox properties, (ii) chemical reactivity and (iii) magnetic properties, but also (iv) in the possible tailoring of their structures and properties by chemical modification of chemical groups present on the molecule without altering the nitroxide function. [8] The nitrogen hyperfine coupling (a N ) is sensitive to the local polarity and to hydrogen bonding, with an approximate change in the a N value by % 15 % (0.1 to 0.2 mT) when comparing EPR spectra from pentane and water solutions. [6] For this last example, nitroxides have demonstrated to be powerful reporter molecules due to 3 main categories of information that can be gained from the analysis of their Electron Paramagnetic Resonance (EPR) spectra, i. e. motional dynamics, local environment, and sensitivity of detection.…”
Section: Overview Of Nitroxides Applicationsmentioning
confidence: 99%
“…The few known examples include a CB [8]@dinitroxide crystal, [20] TEMPAM with CB [7] and also with CB[8] [21] and a {CB[8]@nitroxide} 3 triangle [22] that will be discussed later. The few known examples include a CB [8]@dinitroxide crystal, [20] TEMPAM with CB [7] and also with CB[8] [21] and a {CB[8]@nitroxide} 3 triangle [22] that will be discussed later.…”
Section: Solid State and Magnetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation